2013
DOI: 10.1002/mabi.201200471
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin‐Methacrylamide Hydrogels as Potential Biomaterials for Fabrication of Tissue‐Engineered Cartilage Constructs

Abstract: Gelatin-methacrylamide (gelMA) hydrogels are shown to support chondrocyte viability and differentiation and give wide ranging mechanical properties depending on several cross-linking parameters. Polymer concentration, UV exposure time, and thermal gelation prior to UV exposure allow for control over hydrogel stiffness and swelling properties. GelMA solutions have a low viscosity at 37 °C, which is incompatible with most biofabrication approaches. However, incorporation of hyaluronic acid (HA) and/or co-deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
674
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 694 publications
(703 citation statements)
references
References 52 publications
28
674
0
1
Order By: Relevance
“…A standardized testing protocol consisting of rheological and mechanical assessments was used to compare three commercially available bioinks to Vivoflow, which was physically crosslinked with cations for one and 24 h [14]. The commercial bioinks are referred to based on their main composition as Gel-MA (10% gelatin methacrylate [5,18,19] photo-crosslinked with 0.05% Ircacure I2959, BioGel from BioBots), PEG-DA (polyethyleneglycol-diacrylate photo-crosslinked with photoinitiator, BioInk from regenHu AG, [20] and NC-Alg (1.36% nanocellulose and 0.5% alginate crosslinked with cationic solution, Cellink from Cellink) [21]. The rheological tests included shear behavior with yield point measurements ( Figure 4A) and shear recovery analysis by two shear cycles ( Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…A standardized testing protocol consisting of rheological and mechanical assessments was used to compare three commercially available bioinks to Vivoflow, which was physically crosslinked with cations for one and 24 h [14]. The commercial bioinks are referred to based on their main composition as Gel-MA (10% gelatin methacrylate [5,18,19] photo-crosslinked with 0.05% Ircacure I2959, BioGel from BioBots), PEG-DA (polyethyleneglycol-diacrylate photo-crosslinked with photoinitiator, BioInk from regenHu AG, [20] and NC-Alg (1.36% nanocellulose and 0.5% alginate crosslinked with cationic solution, Cellink from Cellink) [21]. The rheological tests included shear behavior with yield point measurements ( Figure 4A) and shear recovery analysis by two shear cycles ( Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, stem cell is an alternative cell source for cartilage biofabrication attributing to its differentiation ability. Schuurman et al fabricated a grid-like structure, where chondrocytes embedded in GelMA showed the viability of 82% in 3 days of culture [59]. With regard to 3D bioprinting of cartilage tissue, suitable bioinks with high biocompatibility appeared to be particularly important.…”
Section: Bioprinting Of Cartilagementioning
confidence: 99%
“…These studies also demonstrated the possibility to determine and to reduce the shear stresses transmitted to the cells through experimental and numerical studies [17,19,30,46,127]. To address the unique requirements of extrusion bioprinting regarding the print fidelity and biological characteristics, research efforts have been focused on the development of bioinks exhibiting appropriate rheological, mechanical and biological properties [28,32,74,82,100,152,169,174]. A multitude of crosslinking mechanisms, including thermal gelation, ionic and photocrosslinking, have also been explored to induce the in situ gelation of printed materials with the ultimate goal of improving the mechanical properties, the shape fidelity and the formation of interconnected 3D pores throughout the construct [4,28,107], which still remains a major challenge.…”
Section: Extrusion Bioprintingmentioning
confidence: 99%
“…A major challenge in skin bioprinting, is designing suitable bioinks to produce 3D cellular constructs with intricate geometries, shape fidelity, and high resolution in the placement of cells. In the biofabrication field, traditional approaches to generate such constructs often involve (1) the sequential printing of cell-laden hydrogels or melt extruded thermoplastic fibres, (2) the formulation of viscous bioinks by adding high molecular weight polymers (e.g., hyaluronic acid, HA), or (3) the use of increased polymer concentrations and crosslinking densities [152,173,174,193]. The combination of hydrogel bioprinting with melt extrusion has been successfully explored to design well-defined 3D constructs with improved mechanical properties, which is of special interest for load bearing tissues [80], but of limited application in soft tissues.…”
Section: Hydrogel Bioinksmentioning
confidence: 99%